2014
DOI: 10.1007/s00167-014-3395-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of 3.0 T magnetic resonance imaging for the detection of meniscus posterior root pathology

Abstract: Prognostic study (diagnostic), Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
74
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 35 publications
0
74
1
2
Order By: Relevance
“…Many authors have reported the presence of degeneration in the posterior region of the medial meniscus in patients with knee OA [1113]. We considered that Japanese patients with knee OA are likely to have different characteristics than Westerners because of the differences in lifestyles and body types between these two populations.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have reported the presence of degeneration in the posterior region of the medial meniscus in patients with knee OA [1113]. We considered that Japanese patients with knee OA are likely to have different characteristics than Westerners because of the differences in lifestyles and body types between these two populations.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is an important tool for evaluating meniscus integrity. In the detection of LMPRTs using MRI, sensitivity is 0.600, specificity is 0.903, positive predictive value is 0.181, and negative predictive value is 0.984 . Additional findings to aid LMPRT diagnosis with MRI should improve diagnostic accuracy.…”
mentioning
confidence: 99%
“…The QUADAS quality bias and checklist tool is heavily weighted towards assessing bias, as question items 3, 4, 5, 6, 7, 10, 11, 12 and 14 assess bias and two question items 1 and 2 are related to variability [4]. From an accuracy perspective, basing diagnostic values on specificity and sensitivity alone could be a limitation as heterogeneous nature of meniscal tears (anterior versus posterior tears) including different patient contexts and meniscal pathologies could dramatically alter levels of sensitivity and specificity values [27].…”
Section: Limitations Of This Reviewmentioning
confidence: 99%
“…Research has demonstrated that injuries which occur within avascular regions of the menisci do not heal spontaneously [3]. Early detection of meniscal injuries is therefore of paramount importance to enable rapid implementation of appropriate treatment interventions and to reduce the risk of complications [4]. Identifying clinically useful methods for detecting meniscal tears has therefore attracted much attention from physiotherapists and doctors for many years [5].…”
Section: Introductionmentioning
confidence: 99%